How to de-risk: European economic security in a world of interdependence - Jean Pisani-Ferry; Beatrice Weder; Jeromin Zettelmeyer (Bruegel, 2024)
Pandemic-related supply disruptions, the energy crisis provoked by Russia's invasion of Ukraine and economic coercion by China have put economic security high on the European Union policy agenda. The question is how exactly the EU should 'de-risk' its external economic relationships without foregoing the benefits of trade. The standard answer is that it should identify product-level trade dependencies, mainly on the import side, and reduce them, mainly through diversification of suppliers, while otherwise maintaining maximum trade integration. This Policy Brief argues that this answer falls short. First, product-level dependencies cannot be identified reliably even with sophisticated analysis and data. As a result, both 'missed dependencies' and 'false positives' are inevitable. Second, external shocks and coercion could be propagated through exports, productive assets held abroad and financial channels as much as through imports. The analysis has five main implications Import de-risking should focus on a few product categories for which the costs of supply interruptions would be unquestionably large. This reduces false positives. De-risking and/or buffers to deal with exports and financial coercion require more attention. De-risking must be complemented by raising resilience against all shocks, whatever theirorigin. This requires a deeper and broader European single market. De-risking and resilience must be complemented by deterrence. A sufficiently high probability of chronic trade conflict - or one very large conflict - mayjustify reducing overall integration with a large trading partner, on both the export andimport sides. EU economic security policies have been right to emphasise the reduction of import dependence on chips and critical raw materials, and the creation of a powerful legal instrument to deter coercion (the Anti-Coercion Instrument). In most other respects, there is room for improvement.
Keywords: 330; EU-China relations; trade policy